2012
DOI: 10.1002/jpln.201100262
|View full text |Cite
|
Sign up to set email alerts
|

Combination of electromagnetic induction and gamma spectrometry using K‐means clustering: A study for evaluation of site partitioning

Abstract: Today rapid survey methods of proximal soil sensing (PSS) provide an increasing number of different and highly resolved data. These multidimensional data sets can lead to multilayered and complex maps of parameters which are only indirectly related to soil properties and soil functions. However, in applications usually just one clear elementary map is required. It is of increasing importance to tackle this problem utilizing a cluster algorithm for the synthesis and reduction of multidimensional input variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Therefore, we use selected variables from both methods for a joint analysis based on a cluster algorithm in order to identify zones of similar soil conditions. The so-called zonal approach (based on e.g., k means or fuzzy c means clustering) has become a common tool in geophysical data analysis for delineating subsurface structures and estimating petrophysical parameters (e.g., Tronicke et al, 2004;Dietrich and Tronicke, 2009;Paasche et al, 2010;Altdorff and Dietrich, 2012). We chose k means clustering because of its simple performance and robust results, using the software Systat.…”
Section: Hill-slope Characterisation and Partitioningmentioning
confidence: 99%
“…Therefore, we use selected variables from both methods for a joint analysis based on a cluster algorithm in order to identify zones of similar soil conditions. The so-called zonal approach (based on e.g., k means or fuzzy c means clustering) has become a common tool in geophysical data analysis for delineating subsurface structures and estimating petrophysical parameters (e.g., Tronicke et al, 2004;Dietrich and Tronicke, 2009;Paasche et al, 2010;Altdorff and Dietrich, 2012). We chose k means clustering because of its simple performance and robust results, using the software Systat.…”
Section: Hill-slope Characterisation and Partitioningmentioning
confidence: 99%
“…More recently, gamma‐ray ( γ ‐ray) data (e.g. potassium [K] – % and total count [TC] – cps) have been used in combination with EC a to identify zones (Altdorff & Dietrich, ). In this regard, Huang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of ancillary data in soil mapping is evident, mostly in EMI (e.g. Islam et al ., ) but increasingly in γ ‐ ray data (Wilford & Minty, ), and where these data are being used to identify soil management zones (Altdorff & Dietrich, ; Van Meirvenne et al ., ). Recently, Huang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of ancillary data in soil mapping is evident, mostly in EMI (e.g. Islam et al, 2011) but increasingly in c-ray data (Wilford & Minty, 2006), and where these data are being used to identify soil management zones (Altdorff & Dietrich, 2012;Van Meirvenne et al, 2013). Recently, Huang et al (2014) showed how fuzzy kmeans (FKM) clustering of EMI and c-ray could be used to identify soil types that were related to geology for two fields in Nottinghamshire, UK.…”
Section: Introductionmentioning
confidence: 99%